Development Demands Innovation - Teodora ABRAMIUC (TODORAN); Gheorghe-Alexandru STATIVĂ (Communications of International Proceedings, 2021)
In the current paper the Learning and Teaching topic will be treated as a journey. The kickoff research is originating in a focused understanding of the demand, conducted through an individual training needs analysis. That first step of the research would provide the needed input and insights for better understanding the developmental areas and the gaps resulting from such lack of skills. Basis that analysis and learning readiness, the paper is proposing a set of various innovative techniques and activities to bridge those gaps and fulfill the needs of the professionals. This research is focusing on the European demand and practices, with a community targeted in the outsourcing industry. Similarly, the innovations proposed are in line with the demand and the proposed aspects become a good example of potential new practices for the much-needed eLearning techniques, across industries.
Keywords: E-Learning; Innovation in Education; New Technology.